2005
DOI: 10.1258/0049475054620879
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rheumatic fever and rheumatic heart disease in rural Bangladesh

Abstract: A community-based study was done on 5923 rural Bangladeshi children aged 5-15 years to determine the prevalence of rheumatic fever (RF) and rheumatic heart disease (RHD). The prevalence was found to be 1.2 (95% confidence interval 0.3-2.1) per 1000 for RF defined by revised Jones criteria and 1.3 (0.4-2.2) per 1000 for Doppler echocardiography-confirmed RHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 3 publications
1
32
0
Order By: Relevance
“…1 In the present study, young age and female preponderance were observed. All patients had severe mitral stenosis.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…1 In the present study, young age and female preponderance were observed. All patients had severe mitral stenosis.…”
Section: Discussionsupporting
confidence: 57%
“…In a more recent community based study on 5925 rural Bangladeshi children aged 5-15 years, the prevalence of rheumatic fever and rheumatic heart disease was found to be 1.2 per 1000 for rheumatic fever defined by Revised Jones Criteria and 1.3 per 1000 for Doppler echocardiographydefined rheumatic heart disease. 1 Although the pathogenesis of pulmonary function abnormality in mitral stenosis is not fully known, it is certain that the chronic changes in pulmonary circulation secondary to increased pulmonary venous pressure and reflex pulmonary artery vasoconstriction cause alterations in pulmonary vessels and in the composition of lung tissue. 2 Accumulation of water, proteins, and proteoglycans in the interstitium has been acknowledged in this condition.…”
Section: Introductionmentioning
confidence: 99%
“…Five population-based prevalence studies of rheumatic heart disease in school-aged children were found from SouthCentral Asia since 2003, [3][4][5][6][7] along with 1 from China 8 and 1 from Asia Other. 9 Interestingly, 4 of 5 recent studies from South-Central Asia produced prevalence estimates substantially lower (range 0.68 to 1.3 per 1000) than the pooled estimate from this region in the previous review (2.2 per 1000), although 1 study from Pakistan gave a much higher estimate (between 7 and 12 per 1000).…”
Section: Resultsmentioning
confidence: 99%
“…Data regarding the incidence and prevalence of these conditions vary widely. [36][37][38][39][40][41][42] (Table 3). However, over the past 3 decades, there is a declining trend of acute RF in the country.…”
Section: Methodsmentioning
confidence: 99%